Effect of the gate electrodes/water interface on the performance of ZnO-based water gate field-effect transistors - Ozório, Maíza S. [UNESP]; Vieira, Douglas H. [UNESP]; Nogueira, Gabriel L. [UNESP]; Martin, Cibely S. [UNESP]; Alves, Neri [UNESP]; Constantino, Carlos J.L. [UNESP] (Elsevier, 2022)
Field-effect transistors can be gated with water as the dielectric due to the formation of electrical double layers at water interfaces, which results in high specific capacitance and low voltage operation. The incorporation of analytes in aqueous suspension influences the water's electrical properties changing the water-gated field-effect transistors (WGFETs) performance and allowing it to be used as sensor and biosensor platforms. However, the material used as a gate electrode can affect the transistor's performance due to several factors, as the metal work function, its electrochemical range, and the presence of physicochemical reactions. Here, we evaluated the performance of WGFETs using spray-deposited zinc oxide (ZnO) as the active layer and five different gate electrodes: graphite pencil (GP), gold (Au), indium tin oxide (ITO), tungsten (W), and tin (Sn). The threshold voltage (VTH) values found were 0.41, 0.44, 1.12, 1.21 and 1.74 V for the Sn, W, Au, GP and ITO electrodes, respectively. The field-effect mobility was strongly influenced by the gate material, varying in the range from 0.07 to 0.46 cm2/Vs. The WGFETs operating with W and Sn gates showed the highest Ion/Ioff ratio and the lowest VTH when compared to the other electrodes. However, this characteristic may be associated with the formation of a natural oxide layer at its interface with water, which could be undesirable from the stability view. The use of ITO as the gate electrode resulted in a large hysteresis and two orders of magnitude smaller current in the output curve compared to Au and GP. Among the materials used as the gate electrode, GP stands out mainly because it gives the lowest subthreshold swing (SS = 90 mV/dec) and the highest transconductance (gm = 0.40 mS). Also, the GP matches with ZnO as biocompatible material for low-cost, eco-friendly, and metal-free electronics. In summary, the results showed that the gate electrode significantly influences the main parameters of the device and, therefore, should be an analysis factor when aiming to use WGFETs as sensors.
Keywords: Capacitance; Electrical double layers; Electrolyte; Gate electrode; Water-gated field-effect transistors; ZnO